Restoring Humanity Through Environmental Ethics: A Moral Solution to Human Negligence Towards Nature - Mohammed, Yakubu Zulaihat; Muhammad, Adamu Abubakar; Zaki, Salisu Abba; Abdullahi, Hashimu (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2025)
Human greed, carelessness, and a lack of moral concern for other living things have undermined the vital connection that exists between humans and the environment. Pollution, deforestation, and careless garbage disposal are just a few examples of how far society has strayed from its moral obligation to protect the environment. The goal of this study is to investigate how moral and ethical principles can be applied to rectify environmentally harmful human attitudes. The study's primary goal is to advance environmental ethics as a means of resurrecting human empathy and accountability for all living things. Using a qualitative approach, books, journal articles, passages from the Qur'an, and prophetic traditions emphasizing moral behaviour and earth stewardship were reviewed. Results show that environmental degradation is not just a physical problem but also a moral one brought on by ignorance, greed, and a lack of empathy. According to the study, people are more inclined to preserve and defend the environment when they see it through the prism of humanity and divine trust. Therefore, the work suggests that public awareness campaigns be used to support the inclusion of environmental ethics in moral and religious education at all levels. It suggests that people, educators, and religious organizations collaborate to create a culture of environmental responsibility and compassion for all living things, concluding that true humanity is reflected in genuine care for the environment.